Kontruksi Arisan Manakib Abdul Qadir Al-Jilani Sebagai Basis Soliditas Moderasi Beragama Remaja Desa Sraten Banyuwangi - Fawait Syaiful Rahman (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
Abdul Qadir al-Jilani's social gathering activities as a basis for strengthening religious moderation brought tremendous changes to the attitudes, behaviors, and activities of adolescents. They are increasingly diligent in their activities to prayer rooms and mosques, as well as attracting the attention of parents to participate in the event. This study discusses the chronology, construction, and implications of Abdul Qadir al-Jilani's arisan tradition as a basis for strengthening adolescent moderation in Sraten village. The research method used is qualitative with the type of field research. Data collection methods use interviews, documentation, and observation, data analysis uses data reduction, data display, and conclusions. The result of the study was the tradition of the Shaik Abdul Qadir al-Jilani manakib arisan motivated by the extreme behavior of Sraten village teenagers in the form of beating some people with the status of the MD-affiliated al-Furqan mosque committee. Youth leaders and community leaders initiated to embrace the teenagers following Manakib Shaykh Abdul Qadir al-Jilani which was packed with mobile gatherings. The tradition of menakib arisan is a term for the institutionalization of Manakib Shaykh Abdul Qadir al-Jilani in a society with a social gathering system. The tradition of Shaykh Abdul Qadir al-Jilani's social gathering takes the form of a traveling gathering reading and translating the manakib of Manakib Shaykh Abdul Qadir al-Jilani. This activity brought a change in the attitude and behavior of teenagers from before and after following the tradition of Abdul Qadir al-Jilani's arisan. Moderate behavior change based on non-violence indicators so that the conflict over the al-Furqan mosque house of worship was resolved through a lawsuit to the Surabaya State Administrative Court.